2019
DOI: 10.1177/0269758019833284
|View full text |Cite
|
Sign up to set email alerts
|

Group identity, empathy and shared suffering: Understanding the ‘community’ impacts of anti-LGBT and Islamophobic hate crimes

Abstract: This article examines the indirect impacts of hate crimes on lesbian, gay, bisexual and transgender and Muslim communities in the United Kingdom. Based on 34 qualitative interviews, we explore both the perceived meaning of ‘community’ in the context of targeted victimization and the emotional and behavioural effects that anti-lesbian, gay, bisexual and transgender and Islamophobic hate crimes have on other members of the victim’s group. Building on previous quantitative data undertaken as part of a larger prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…LGBT and Muslim people which found that knowing other people who have been the victim of hate crime increases the perception of threat in those indirect victims. This in turn is linked to heightened feelings of vulnerability, anxiety and anger (Paterson et al, 2018;Walters et al, 2020). These heightened emotions are evidence of the terrorising effects of hate crime, on the broader community of which the victim is part: what the European Union Agency for Fundamental Rights (FRA) refers to as the "resonating nature of hate crime" (European Union Agency for Fundamental Rights, 2012, p. 18), or what Perry and Alvi have referred to as the "in terrorem" effect of hate crime (Perry & Alvi, 2012, p. 57).…”
Section: Understanding Hate (Crime)mentioning
confidence: 99%
“…LGBT and Muslim people which found that knowing other people who have been the victim of hate crime increases the perception of threat in those indirect victims. This in turn is linked to heightened feelings of vulnerability, anxiety and anger (Paterson et al, 2018;Walters et al, 2020). These heightened emotions are evidence of the terrorising effects of hate crime, on the broader community of which the victim is part: what the European Union Agency for Fundamental Rights (FRA) refers to as the "resonating nature of hate crime" (European Union Agency for Fundamental Rights, 2012, p. 18), or what Perry and Alvi have referred to as the "in terrorem" effect of hate crime (Perry & Alvi, 2012, p. 57).…”
Section: Understanding Hate (Crime)mentioning
confidence: 99%
“…While the concept of hate crime has not been narrowly defined, and measurement challenges persist, what we do know is that when an individual is the subject of targeted violence, the impacts can be considerable. It is accepted internationally that hate crime is likely to have a more significant impact on its victims than non-hate motivated offences (Iganski, 2008;Paterson et al, 2019;Walters, 2020). Direct impacts can range from physical injury to emotional and psychological harm.…”
Section: Impacts Of Hate Crimementioning
confidence: 99%
“…However, forming such globalized connections with peers whom participants are intimately connected with, through their shared oppressed identities, allows for a globalization of victimization. Indeed, Walters et al (2020) articulate that enhanced levels of empathy are found when hate crimes occur, giving rise to a sense of 'shared suffering' and a global connection to group members through common experiences of prejudice and hate. This is evidenced acutely by Sue's (YCW, cis 3 woman, lesbian, aged 48) interview, which highlighted that many of the LGBTþ people she knows and works with have high levels of anxiety due to the globalized manner in which victimization of LGBTþ people is shared across social media.…”
Section: Social Media Use and Elevated Anxietymentioning
confidence: 99%
“…reading names of dead victims and discussing traumatic events) due to the personal and sensitive nature of the vigil. Despite this, the news of Orlando prompted a level of resistance and politicization in the aftermath of the events, to stand in solidarity with LGBTþ Floridians as a global community (Walters et al, 2020). Ruth goes on to describe how the attendance of her local Pride event -which ran a month after the Orlando shooting -was affected:…”
Section: Resistance and Remembrancementioning
confidence: 99%